Germline variant testing in serrated polyposis syndrome. Issue 5 (18th February 2022) - Murphy, Aisling; Solomons, Joyce; Risby, Peter; Gabriel, Jessica; Bedenham, Tina; Johnson, Michael; Atkinson, Nathan; Bailey, Adam A; Bird‐Lieberman, Elizabeth; Leedham, Simon J; East, James E; Biswas, Sujata
Abstract: Background and Aim: Serrated polyposis syndrome (SPS) is now known to be the commonest polyposis syndrome. Previous analyses for germline variants have shown no consistent positive findings. To exclude other polyposis syndromes, 2019 British Society of Gastroenterology (BSG) guidelines advise gene panel testing if the patient is under 50 years, there are multiple affected individuals within a family, or there is dysplasia within any of the polyps. Methods: A database of SPS patients was established at the Oxford University Hospitals NHS Foundation Trust. Patients were referred for genetic assessment based on personal and family history and patient preference. The majority were tested for a hereditary colorectal cancer panel including MUTYH, APC, PTEN, SMAD4, BMPR1A, STK11, NTLH1, POLD1, POLE, GREM1 (40‐kb duplication), PMS2, and Lynch syndrome mismatch repair genes. Results: One hundred and seventy‐three patients were diagnosed with SPS based on World Health Organization 2019 criteria between February 2010 and December 2020. The mean age of diagnosis was 54.2 ± 16.8 years. Seventy‐three patients underwent genetic testing and 15/73 (20.5%) were found to have germline variants, of which 7/73 (9.6%) had a pathogenic variant (MUTYH n = 2, SMAD4 n = 1, CHEK2 n = 2, POLD1 n = 1, and RNF43 n = 1). Only 60% (9/15) of these patients would have been recommended for gene panel testing according to current BSG guidelines. Conclusions: A total of 20.5% of SPS patients tested were affected by heterozygous germline variants, including previously unreported associations with CHEK2 and POLD1. This led to a change in management in seven patients (9.6%). Current recommendations may miss SPS associated with germline variants, which is more common than previously anticipated.